PENGARUH PEMUPUKAN PADA LAHAN GAMBUT TERHADAP KARAKTERISTIK TANAH, EMISI CO2, DAN PRODUKTIVITAS TANAMAN KARET - Salma J Fitra; Sugeng Prijono; M Maswar (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
The limited availability of productive agricultural land causes the development of agriculture leading to the marginal lands, one of which is peat land. Peat land is land with soil that is rich in organic matter (C-organic >18%), and relatively has low level of fertility. Based on the characteristics of peat, fertilization needs to be done to support plant growth. One of the plant that can grow and adapt on peat land is rubber plant. Fertilization can also potentially increase the process of decomposition of peat so that can increase CO2 emission which is one of the greenhouse gases.The purpose of this study was to analyse the effect of fertilization on peat land to soil characteristics, CO2 emission, and rubber plant productivity. This study used a randomized block design with four treatments and four replications. The treatments were P0 (control/base fertilizer Urea, SP-36, and KCl), P1 (control + cow manure), P2 (control + borax fertilizer), and P3 (control + cow manure + borax fertilizer). The results showed that fertilizer with combination of control and cow manure (P1) significantly affected the soil chemical characteristics such as CEC, N total, K-exch, and P availability. The P1 treatment also tended to increase the increasing of stem circumference for 9 months period. However, in the other parameters such as soil bulk density, ash content, pH, base saturation, base cations exchangeable (Ca, Mg, Na), C-organic, CO2 emission, and latex production, showed that fertilization combination treatment did not give any significant differences. In general, fertilization treatment with the combination of control and cow manure (P1) had the best effect of improving soil chemical characteristics.